The acute effect of match play on hamstring strength and lower limb flexibility in elite youth football players - Wollin, M.; Thorborg, K.; Pizzari, T. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of this study was to investigate the effect of competitive football match play on hamstring strength and lower limb flexibility. Fifteen male international youth football players were included. Hamstring strength and associated pain ratings, ankle dorsiflexion, hip extension, knee extension and flexion range of motion were evaluated immediately post-match and at intervals of 24, 48, and 72 h post-match. Strength significantly reduced post-match (P < 0.01), mean difference -0.43 (CI95: -0.56, -0.30) and 24 h post (P < 0.05) mean difference -0.12 Nm/kg (CI95: -0.20, -0.04). The associated pain scores significantly increased at the post-match (P < 0.01, ES = 0.61) and 24 h (P < 0.01, ES = 0.55) time intervals. At the 48 and 72 h post-match tests no significant difference was found for strength or pain ratings. No significant differences were detected for any of the range of motion measures. Competitive football match play has a significant acute and transient effect on isometric hamstring strength and associated pain levels during resisted knee flexion in male international youth players. Range of motion measures appear to remain relatively unaffected by match play. Isometric hamstring strength testing and associated pain levels might be considered for inclusion in-season to monitor player's post-match hamstring recovery characteristics.